IMPLEMENTASI METODE FUZZY MULTI CRITERIA MAKING (FMCDM) UNTUK OPTIMALISASI PENENTUAN LOKASI PERUMAHAN - Maryaningsih, Maryaningsih; Mesterjon, Mesterjon (UNIVED Press, 2012)
The choice of location for optimalisai business activities such as site selection perumahn, factories, etc. are determined through mechanisms and patterns that can be understood. Various criteria are taken into account in determining the location include availability of land, raw materials, distance, accessibility, transportation, labor, security, local market absorption, political stability, and other supporting facilities.Some general location theory approach to minimize wear costs, maximize profits, market approach, attraction or gravity. One effort to help ease the employer or the manufacturer in the decision to determine the optimal location of housing is to build the software (software) applications of artificial intelligence based on fuzzy multi-Criteria Decision Making (FMCDM).Determination of the optimal residential location decisions based on criteria specified by the employer. So employers particularly in deveoper / developers do not bother anymore to find or obtain information about the location of residential development in the desired by consumers, and can reduce the risk of unwanted and time savings.